Canola oil and olive oil impact on lipid profile and blood pressure in women with type 2 diabetes: a randomized, controlled trial - Atefi, Masoumeh; Pishdad, Gholam Reza; Faghih, Shiva (Progress in Nutrition, 2018)
Objective: A number of studies indicated that olive oil (OO) and canola oil (CO) have lipid-lowering and blood pressure-lowering effects. This clinical trial was done to compare the effects of CO and OO on serum lipids and blood pressure in women with type 2 diabetes. Methods: This randomized controlled clinical trial was done on 77 type 2 diabetic women. 4 weeks before the intervention, lipid-lowering drugs intakes were cut under the supervision of an endocrinologist. The participants were randomly allocated into 2 intervention groups (Balanced diet + 30 grams/day OO or CO) and one control group (Balanced diet + 30 grams/day of sunflower oil (SFO)). Dietary intakes were assessed using three 24-hour food records at baseline and at weeks 4 and 8 of the interventions. At baseline and after 8 weeks, height, weight, waist circumference, systolic blood pressure (SBP), diastolic blood pressure (DBP), serum total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), very low-density lipoprotein (VLDL-C) and high-density lipoprotein cholesterol (HDL-C) were measured and the data were statistically analyzed by SPSS 19. Results: After treatment, SBP (p=0.02), TG (p=0.01) and VLDL-C (p=0.02) were significantly decreased in OO group. None of the variables had significant changes in CO or SFO groups. There were no significant differences in the blood pressure and lipid profile among 3 groups. Conclusion: Although we found no differences between the effects of CO, OO, and SFO, it seems that replacing CO and SFO by OO may have some beneficial effects on SBP, TG and VLDL-C in women with type 2 diabetes.